2010
DOI: 10.1016/s0924-9338(10)70344-8
|View full text |Cite
|
Sign up to set email alerts
|

P01-139 - Social Anxiety among Medical Undergraduate Students in Malaysia

Abstract: Objectives: To study the prevalence of social anxiety problem and potential risk factors that may be associated with social anxiety among Malaysian medical undergraduate students. Methods: Social Phobia Inventory (SPIN) and a questionnaire assessing gender, religion, number of siblings, type of previous school and partner status were given to 167 final year medical students at University Malaya. Results: There were 101 respondents of which 56% of the medical students scored > 19 in the Social Phobia Inventory … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 0 publications
0
4
2
Order By: Relevance
“…These include sleep duration, communication problems with teaching staff, feelings of inferiority, and family problems (Nayak, 2021). In addition, several studies found a statistically significant association between gender and social anxiety, although no such association was reported in the current study [31,33], which may be attributed to the small sample size. A range of factors have been associated with social anxiety in healthcare professionals, including age, history of chronic illness, academic performance satisfaction, language barrier, and increasing academic years of exposure [6,7].…”
Section: Discussioncontrasting
confidence: 98%
See 2 more Smart Citations
“…These include sleep duration, communication problems with teaching staff, feelings of inferiority, and family problems (Nayak, 2021). In addition, several studies found a statistically significant association between gender and social anxiety, although no such association was reported in the current study [31,33], which may be attributed to the small sample size. A range of factors have been associated with social anxiety in healthcare professionals, including age, history of chronic illness, academic performance satisfaction, language barrier, and increasing academic years of exposure [6,7].…”
Section: Discussioncontrasting
confidence: 98%
“…It was estimated that the prevalence of social anxiety in Saudi Arabia was roughly 51% among medical students, with 8% and 4% reporting severe and very severe social anxiety [30]. Research has consistently shown a high prevalence of social anxiety among medical students, with some studies reporting rates as high as 56% [31,32]. In Czech, a study showed that 85% of Czech medical students showed some symptoms of avoiding behavior, and 56% experienced somatic symptoms of social anxiety.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The prevalence rate of 33.6% for SAD reported in this study is lower than the 56% recorded in Malaysia by Gill & Mohammad (2010). Again, SAD and panic disorder appeared significantly related to the year of study.…”
Section: Discussioncontrasting
confidence: 77%
“…Based on another study on the prevalence of social anxiety among undergraduate health science students in Gondar, 32.1% of the students experienced social anxiety from mild to severe anxiety (Hakami et al, 2018). A similar study among Malaysian medical undergraduates showed that 56% of the medical student experienced social anxiety symptoms (Gill & Mohammad, 2010). Students with positive social anxiety usually face significant disabilities in conducting or maintaining their work, social life, and mental health.…”
Section: Literature Reviewmentioning
confidence: 97%